Avaliação da influência da agitação ultrassônica no pH e na atividade antibiofilme de cimentos obturadores endodônticos – estudo In vitro - Viana, Francisca Lívia Parente (2024)
The present study aimed to evaluate, in vitro, the influence of ultrasonic agitation on the pH and antimicrobial activity of the endodontic sealers AH Plus Jet (AHP) and BioRoot RCS (BCS). Experimental groups were defined according to the sealer and the use or not of ultrasonic agitation (UA). The latter, when applied, was performed by means of a smooth conical insert inserted into the mass of the materials in two agitation cycles of 20 seconds. The antimicrobial activity was determined by direct contact (TCD), indirect contact (TCI) and bacterial viability, both for total count and by microbial species. The pH determination was performed by means of a pH meter at periods of 30 minutes, 3, 24, 72 and 168 hours. For the contact tests, dual-species biofilms of E. faecalis and S. oralis were formed on human dentin blocks (n = 10) for 21 days; The contact time in both was 24 hours. Bacterial survival was determined by counting colony-forming units (CFUs). Fifty single-rooted human teeth were used to determine bacterial viability. After a period of 21 days of contamination with the dual-species biofilm, the specimens were randomly divided into the experimental groups and a control (n = 10). The specimens were instrumented with the Reciproc system, filled using the single-cone technique, and incubated for a period of 30 days; the control consisted of teeth filled only with gutta-percha. Microbiological samples were collected to count CFUs in the following phases: before (C1) and after instrumentation (C2), after unfilling (C3), and 7 days after removal of the filling material (C4). After the last collection, the roots were sectioned longitudinally in the vestibular-palatal direction and stained with the LIVE/DEAD fluorophore to evaluate bacterial viability by confocal laser scanning microscopy (CLM). Statistical analysis was performed using the Kruskal-Wallis and Dunn tests, both with significance set at 5.0%. The BCS cement presented the highest pH values in all periods analyzed, being significantly higher than those of AHP (P <0.05); UA promoted a reduction in the pH of the sealer at 24 and 72 hours (P <0.05). In the TCD, the BCS groups, with or without UA, provided a significant reduction in the total bacterial count compared to the AH/AU and control groups (P <0.05). In the TCI, the BCS groups presented the best results compared to the control, both in the total bacterial count and E. faecalis (P <0.05). In the bacterial survival test, after desobturacion, with the presence of substrate, the two strains grew approximately 300% in similar quantities (C4/C3); as for the groups, no significant differences were identified between them (P > 0.05). The AHP sealer, with or without UA, when analyzed alone, provided lower bacterial growth in C4 compared to the control (P < 0.05), however, did not present significant difference during the 30-day incubation period. In the cell viability test in MCVL, AHP/UA provided a significant reduction in viable cells of the dual-species biofilm compared to the control group (P < 0.05). Thus, under the conditions of the study, it can be concluded that the BioRoot RCS sealer presented the highest pH values, with ultrasonic agitation reducing its values in the intermediate times. In the contact tests, the same BioRoot RCS showed greater antibacterial action; furthermore, ultrasonic agitation did not promote improvements in antibacterial activity. In the bacterial survival test, AH Plus Jet sealer and ultrasonic agitation, analyzed separately, showed greater antibacterial action against dual-species biofilm of E. faecalis and S. oralis. In MCVL, ultrasonic activation associated with AH Plus Jet sealer provided lower bacterial survival within the dentinal tubules.